Sharenting – the parents’ right or the abuse of the child’s rights? - novakovic, uros (Sociološki pregled, 2025)
The paper analyzes the modern practice of parents who share virtual content about their children on social networks and on online platforms in general (Internet, YouТube...). In legal theory, sharenting is defined as the use of social media by parents for sharing the content about their children via textual posts, photographs and video-clips which contain the child’s personal data. Sharenting is the parents’ authorization, the segment of exercising the parents’ right to fully decide on their own about the child’s visibility on the Internet, without including the child in that decision. The parents’ limited right to publish the content about their child would be reflected in the parents’ posting news about the child on their profiles (that the child was born, that the child started walking, talking, going to the kindergarten or school etc.), but without the visual content accompanying it (photos and videos). In that manner, the child’s identity would not be revealed and, thus, potentially threatened by third parties.
Keywords: child; child’s rights; social media; sharenting; Internet